Analysis of Tryptophan Metabolic Profile Characteristics and Clinical Value in Differentiated Thyroid Cancer Patients - Qiang Miao; Xinhua Dai; Xiaojuan Wu; Li Luo; Junlong Zhang; Han Luo; Bei Cai (Cancer Medicine)
ABSTRACT Background Differentiated thyroid cancer (DTC) is the primary subtype of thyroid cancer. Timely diagnosis and intervention are crucial for improving prognosis and survival. However, the effectiveness of existing serum markers is limited, necessitating the discovery of new biomarkers. Methods This study utilized liquid chromatography–tandem mass spectrometry to analyze tryptophan metabolic profiles in serum samples from 105 DTC patients and 50 healthy controls. Independent predictors of DTC were identified through univariate intergroup comparisons and multivariate logistic regression analysis, leading to the development and validation of a new diagnostic model. Results Significant differences were observed in 11 tryptophan metabolites between DTC patients and controls. Logistic regression identified nicotinamide, 3‐hydroxyanthranilic acid, 5‐hydroxytryptophan, melatonin, and indole‐3‐propionic acid as independent predictors. The nomogram prediction model was established based on these five metabolites, and according to the Hosmer–Lemeshow test, the model showed good fit. The five‐metabolite diagnostic model demonstrated 84.8% sensitivity, 90.0% specificity, and an area under the ROC curve of 0.932. Decision curve analysis indicated that the model had significant advantages over serum thyroglobulin. Discussion Tryptophan metabolism exhibits distinct changes in DTC patients, with specific metabolites serving as early diagnostic markers. The five‐metabolite panel demonstrates potential for improving early detection and management of DTC.